Emphasizing Our Humanity: Interorganizational Collaboration in the DCN during COVID and into the future - Hannah Hadley; Mikala Narlock (Journal of eScience Librarianship, 2023)
Collaboration provides an opportunity to address issues more comprehensively than what is possible by individuals or groups in isolation. Large-scale collaborations, such as those occurring within a network of institutions, can present immense opportunities to solve problems that transcend the local nuances of individual institutions. As we have been reflecting on the experience of collaboration, we wondered—what is the glue that can hold together an intricate web of relationships to meet shared goals or address various challenges? In this column, we draw on four levels of interorganizational collaboration (Schruijer 2021) to assist with organizing and capturing our lived experiences, to center and celebrate the humanity at the core of data curation.